2022
DOI: 10.4103/jfmpc.jfmpc_1998_21
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the outcomes of normal vaginal delivery with and without spinal anesthesia in mothers admitted to the maternity ward of Firoozabadi Hospital

Abstract: Introduction and Objective: The study of the methods of controlling labor pain is very important. One of the methods of pain relief is spinal anesthesia. Due to the different opinions about the effects of spinal anesthesia on the delivery process and maternal and fetal consequences, this study aimed to evaluate the effects of spinal anesthesia and compare it with normal vaginal delivery without spinal anesthesia. Methods: In this retrospective cohort study, 120 mothers,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
(24 reference statements)
0
1
0
Order By: Relevance
“…4,6 Spinal anesthesia has been utilized on pregnant patients during delivery even on a full stomach. 8 In the current article, we present a novel implementation of awake spine surgery in an emergent case of postoperative pSEH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,6 Spinal anesthesia has been utilized on pregnant patients during delivery even on a full stomach. 8 In the current article, we present a novel implementation of awake spine surgery in an emergent case of postoperative pSEH.…”
Section: Discussionmentioning
confidence: 99%
“…[NPO] prior to delivery), no identifiable research articles assess emergency hematoma evacuation by awake spine surgery. 8 However, in cases where a patient is not a good candidate for GA due to loss of NPO status, awake spine surgery can be beneficial. 7…”
Section: Introductionmentioning
confidence: 99%
“…(10) A retrospective cohort study on 120 pregnant women who were divided into 2 groups, with one group receiving spinal anesthesia (n=60) and the other without spinal anesthesia (n=60), showed that the duration of stage II of labor was significantly longer in the women who received spinal anesthesia (p=0.008). (11) The anesthetic drug sufentanil has high solubility, short latency and about 7 hours of action, which makes it a potential effective option for providing fast analgesia. (12) In addition, sufentanil has been reported to cause less respiratory depression than morphine and fentanyl.…”
Section: Introductionmentioning
confidence: 99%